1996
DOI: 10.1111/j.1469-8137.1996.tb01929.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elevated CO2 and grazing by Gastrophysa viridula on the physiology and regrowth of Rumex obtusifolius

Abstract: SUMMARYPlants of Rumex obtusifolius L. were grown in Solardomes under ambient and elevated (+ 250 /;mol mor') mole fractions of CO^ and were exposed to two levels of herbivory by Gastrophysa viridula Degeer larvae. The herbivory treatment lasted 1 month, thereafter half of the plants were harvested and over the following month during a period of regrowth physiological measurements were made on the remaining plants. At the termination of the herbivory treatment uninfested plants showed no damage, whereas the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Symbols for comparison of treatments on specific harvest dates: NS (not significant), *0.05>P>0.01, **0.01>P>0.001, ***P<0.001 Therefore, CO 2 stimulated regrowth independently of the effects of CO 2 on pre-clipping size. Other studies have that found CO 2 stimulates resprouting following defoliation (Fajer et al 1991;Wilsey et al 1994Wilsey et al , 1997Pearson and Brooks 1996) and coppicing (Will and Ceulemans 1997), but in these studies, the effect of CO 2 was not greater for clipped than unclipped individuals. In agreement with the current study, Kruger et al (1998) found the CO 2 effect to be greater for defoliated Acer saccharum.…”
Section: Resultsmentioning
confidence: 92%
“…Symbols for comparison of treatments on specific harvest dates: NS (not significant), *0.05>P>0.01, **0.01>P>0.001, ***P<0.001 Therefore, CO 2 stimulated regrowth independently of the effects of CO 2 on pre-clipping size. Other studies have that found CO 2 stimulates resprouting following defoliation (Fajer et al 1991;Wilsey et al 1994Wilsey et al , 1997Pearson and Brooks 1996) and coppicing (Will and Ceulemans 1997), but in these studies, the effect of CO 2 was not greater for clipped than unclipped individuals. In agreement with the current study, Kruger et al (1998) found the CO 2 effect to be greater for defoliated Acer saccharum.…”
Section: Resultsmentioning
confidence: 92%
“…However, previous herbivory reduces the infection of Rumex leaves by U. rumicis (Hatcher et al 1994, Hatcher andPaul 2000). Air CO 2 content that is expected to increase may also influence leaf acceptability (Pearson andBrooks 1996, Brooks and.…”
Section: G Viridula In Dock Biocontrolmentioning
confidence: 99%
“…Even the seedlings established few weeks before the herbivory, of which 90% leaf area was removed, were able to recover (Hatcher 1996). However, size, root to shoot ratio (Pearson andBrooks 1996, Hatcher 1996), and seed production and quality (Bentley et al 1980) of regrown plants are influenced. Negative effects of herbivory are exaggerated in plants exposed to interspecific Table 6.…”
Section: G Viridula In Dock Biocontrolmentioning
confidence: 99%
“…For example, in future atmospheric conditions, sugar maple might be more capable of tolerating severe defoliation events which in the past have been implicated in widespread maple declines (Houston, 1987). Furthermore, based on data from this and other studies (Ryle & Powell, 1992 ;Pearson & Brooks, 1996), we suggest that the potential of elevated CO # to stimulate plant growth and ecosystem productivity might be fully realized only in the presence of stresses, such as herbivory, that decrease the assimilate source : sink ratio in the plant.…”
Section: Our Findings Indicate That Atmospheric Comentioning
confidence: 99%